Thorsten B. Olesen (red.): Interdependence versus Integration. Denmark, Scandinavia and Western Europe, 1945-1960. Danish Politics in Transition 1945-85. (Odense University Press, 1995). 246 s., 250 kr. - K.N. Midtgaard, Kristine (Historie/Jyske Samlinger, 1998)
-